Colonic Leiomyoma Presenting as Sigmoid Volvulus in a Young Male - Reza Aditya Digambiro; Gerie Amarendra; Florinda Ilona; Julian Chendrasari; Samuel Abiodun Kehinde (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2026)
Colonic leiomyomas are rare tumors that originate from the smooth muscle layer of the colon and are infrequently observed in young individuals. This case report represents a 21-year-old male who presented with a 2-month history of progressive abdominal distension, persistent vomiting, early satiety, and bloating. Computed tomography (CT) of the abdomen suggested sigmoid volvulus with associated bowel obstruction. However, exploratory laparotomy revealed a well-defined, firm intramural mass in the sigmoid colon, leading to segmental resection and primary anastomosis. Histopathological analysis showed intersecting fascicles of bland spindle cells with eosinophilic cytoplasm and cigar-shaped nuclei without atypia or mitotic activity. Immunohistochemistry confirmed positivity for smooth muscle actin (SMA) and negativity for CD117, supporting a diagnosis of colonic leiomyoma and excluding gastrointestinal stromal tumor (GIST). The patient’s postoperative course was uneventful, with complete resolution of obstructive symptoms and restoration of normal bowel function. This case highlights the diagnostic challenge of differentiating colonic leiomyoma from other causes of bowel obstruction, particularly when presenting with features mimicking sigmoid volvulus. It also emphasizes the critical role of histopathology and immunohistochemistry in establishing a definitive diagnosis. Clinicians should consider rare benign tumors in the differential diagnosis of young patients with signs of bowel obstruction.